Comparative Performance of High-Yielding European Wheat Cultivars Under Contrasting Mediterranean Conditions - de Lima, Valter Jário; Gracia-Romero, Adrian; Rezzouk, Fatima Zahra; Diez-Fraile, Maria Carmen; Araus-Gonzalez, Ismael; Kamphorst, Samuel Henrique; do Amaral Júnior, Antonio Teixeira; Kefauver, Shawn C.; Aparicio, Nieves; Araus, Jose Luis (Frontiers in Plant Science, 2021)
Understanding the interaction between genotype performance and the target environment is key to improving genetic gain, particularly in the context of climate change. Wheat production is seriously compromised in agricultural regions affected by water and heat stress, such as the Mediterranean basin. Moreover, wheat production may also limited by the nitrogen availability in the soil. We have sought to dissect the agronomic and physiological traits related to the performance of twelve high-yield European bread wheat varieties under Mediterranean rainfed conditions and different levels of N fertilization during two contrasting crop seasons. Grain yield was more than two times higher in the first season than the second season and was associated with much greater rainfall and lower temperatures. However, the nitrogen effect was rather minor. Genotypic effects existed for the two seasons. While several of the varieties from central/northern Europe yielded more than those from southern Europe during the optimal season, the opposite trend occurred in the dry season. The varieties from central/northern Europe were associated with delayed phenology and a longer crop cycle, while the varieties from southern Europe were characterized by a shorter crop cycle, but a comparatively higher duration of the reproductive period, associated with an earlier beginning of stem elongation and a greater number of ears per area. However, some of the cultivars from northern Europe maintained a relatively high-yield capacity in both seasons. Thus, KWS Siskin from the UK exhibited intermediate phenology, resulting in a relatively long reproductive period, together with a high green area throughout the crop cycle.